Penerapan dan Karakteristik Model Pembelajaran Berbasis Masalah Serta Pengaruhnya terhadap Kemampuan Pemecahan Masalah dan Berpikir Kritis Siswa - Rossa Stevana; Selarista Selarista; Indra Indra (Nubuat : Jurnal Pendidikan Agama Kristen dan Katolik, 2025)
The Problem-Based Learning (PBL) model is a teaching strategy that focuses on students being the main participants in their education by engaging in the resolution of actual problems. This article looks into how PBL is applied in the classroom, its effects on enhancing students' critical thinking abilities, and the primary attributes of this model that aid in developing problem-solving skills. PBL consists of five key phases: identifying a challenge, organizing research efforts, performing both individual and group inquiries, gathering and sharing findings, and reflecting on the process. These phases create a learning experience that promotes teamwork, self-directed research, and thorough analysis of information. Findings from this research reveal that PBL significantly enhances students' critical thinking skills, particularly in areas like analysis, assessment of evidence, solution formulation, and articulating arguments logically. Furthermore, features of PBL, which include prioritizing students, addressing real-world issues, fostering self-directed learning, encouraging group collaboration, and positioning the teacher as a guide, play a crucial role in enhancing problem-solving capabilities. By tackling issues that relate to their daily lives, PBL motivates students to independently build knowledge, foster innovation, and reinforce their autonomy in the learning journey.